Codifying and Validating Management Accounting Practices Measurement Using Content Analysis and Word Embedding Model Using Word2Vec Method - Zahra Khorramdel Masouleh; Amin Nazemi; Navid Reza Namazi (پژوهش‌های تجربی حسابداری)
Management accounting practices play an important role in business management and help companies survive in a competitive and ever-changing world. Appropriate measures of management accounting practices allow academics and practitioners to effectively evaluate the adoption of management accounting practices by companies. In this study, based on the qualitative information disclosed in the annual reports of 175 companies listed on the Tehran Stock Exchange from 2013 to 2022, new and comprehensive criteria for management accounting practices at the company level have been designed using the Word2Vec word embedding model. In measuring textual metrics, using this method is very useful because it can capture the nuances of language and identify patterns in textual data. After developing textual measurement criteria, a series of validations including content validity, convergent validity, discriminant validity and reliability have been performed to confirm that the measurement criteria of management accounting practices really reflect the actual choices of companies. The results show that the fit and approval of the developed measures with the representative indicators of each management accounting practices’ dimensions in the industry indicate the effectiveness of the proposed measures. The new measurement of management accounting practices not only provides a solid foundation for empirical analysis in management accounting research, but also paves a new way to examine the status of companies regarding the extent of using management accounting practices.